THE ASSOCIATION BETWEEN MATERNAL SERUM MAGNESIUM LEVEL AND PREGNANCY OUTCOMES - Jenabi, Ensiyeh; Poorolajal, Jalal; Fereidooni, Bita; Asltoghiri, Maryam; Hejrati, Parisa (Journal of Postgraduate Medical Institute, 2017)
Objective: The aim of this study was to find out the association between maternal serum magnesium levels and preterm labor, neonatal weight, and the duration of labor. Methodology: This observational study was conducted at the Social Security Hospital in Hamadan City, the west of Iran, from October 2014 to January 2015. The case group included 32 preterm labour women (28 to <37 weeks pregnant women) and the control group included 32 term pregnant women. The maternal serum magnesium level, the duration of the first and second stage of labor were measured in both the groups. Results: The duration of gestational age was significantly lower in cases compared to controls (P<0.001). The average birth weight was significantly lower in the case group than in the control group (P<0.001). The mean (SD) level of maternal serum magnesium was 2.12 (0.27) and 1.95 (0.16) in the control and case groups, respectively (P=0.004). The duration of the first stage of labor was lower in the case group than in the control group (P=0.001). There was a positive correlation between maternal serum magnesium level and gestational age (0.3305) and neonatal weight (0.2975) and a negative correlation between maternal serum magnesium level and the duration of the first and second stage of labor (-0.0184 and -0.0445, respectively). Conclusion: Low level of maternal serum magnesium is associated with poor pregnancy outcomes, including preterm labor and low birth weight.